Instrumental and Normative Pathways to Legitimacy and Public Cooperation with the Police in Turkey: Considering Perceived Neighborhood Characteristics and Local Government Performance. (2nd January 2017) - Karakus, Onder
Abstract : This study investigates the relative contributions of instrumental and normative models to the legitimacy of and cooperation with the police in Turkey. Based on a random sample of 1, 800 Istanbulians, the potential contributions of perceived neighborhood characteristics also are considered. Results show that both instrumental and normative models of regulation are applicable to the highly centralized and state-serving Turkish policing context. While the instrumental model exerts relatively more influence on legitimacy than does the normative model, the two models are of equal importance in predicting legitimacy after perceived neighborhood characteristics are taken into consideration. Social cohesion and local government performance also emerged as significant predictors of police legitimacy. Public cooperation with police, on the other hand, is encouraged by increased police legitimacy, better local government performance, and higher household income. Implications for future research and policy are discussed.